M3DITRACK3R: A design of an automated patient tracking and medicine dispensing mobile robot for senior citizens - Kalai Chelvam, Y. (Institute of Electrical and Electronics Engineers Inc., 2014)
Failure to take a medication of the right dosage, at the right time causes minor healthcare problems to become worse. This is extremely problematic for the elderly patients who have difficulties in keeping track of their medicine. Therefore, M3DITRACK3R, an automated medicine dispenser which keep tracks of the dosage and duration between each consumption would be beneficial for senior citizens living independently. Elderly patients that have ageing issues, such as dementia or Alzheimer's disease have difficulties to remember their responsibilities. Poor eyesight as one of the contributors for medicine consumption errors such as misdosage since the elderly finds it troublesome to read the instruction on the medicine case, and identifying the right dosage of the medicine. Physical disabilities such as arthritis makes it difficult for elderly patients to open the cap of a vacuum tight medicine bottle. Hence, this paper presents a robotic application referred as M3DITRACK3R that is able to track the location of patient using the infrared sensor and dispense medicine at the right dosage and at the right time. The hardware and software design are outlined based on critical reviews made over the existing systems. Performance test and user acceptance test have been conducted and satisfactory results are achieved. Â© 2014 IEEE.